2023
DOI: 10.1007/s12032-023-01994-y
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondii-derived antigen modifies tumor microenvironment of Ehrlich solid carcinoma murine model and enhances immunotherapeutic activity of cyclophosphamide

Abstract: Pathogen-based cancer vaccine is a promising immunotherapeutic weapon to stimulate cancer immunosuppressive state. Toxoplasma gondii is a potent immunostimulant, and low-dose infection was linked to cancer resistance. Our goal was to evaluate the therapeutic antineoplastic activity of autoclaved Toxoplasma vaccine (ATV) against Ehrlich solid carcinoma (ESC) in mice in reference to and in combination with low-dose cyclophosphamide (CP), a cancer immunomodulator. Mice inoculation with ESC was followed by applyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…demonstrated that mice immunized with autoclaved Toxoplasma vaccine (ATV) produced 13.3% inhibition of Ehrlich solid carcinoma (ESC) genesis and confirmed the existence of at least four pairs of common antigens between ATV and ESC ( Eissa et al., 2023 ). Subsequent results showed that ATV and cyclophosphamide synergistically exerted a stronger tumor immune response and anti-angiogenesis effect in ESC-bearing mice, indicating that ATV has the potential to be a tumor vaccine or cancer drug adjuvant ( Ismail et al., 2023 ).…”
Section: T Gondiimentioning
confidence: 99%
“…demonstrated that mice immunized with autoclaved Toxoplasma vaccine (ATV) produced 13.3% inhibition of Ehrlich solid carcinoma (ESC) genesis and confirmed the existence of at least four pairs of common antigens between ATV and ESC ( Eissa et al., 2023 ). Subsequent results showed that ATV and cyclophosphamide synergistically exerted a stronger tumor immune response and anti-angiogenesis effect in ESC-bearing mice, indicating that ATV has the potential to be a tumor vaccine or cancer drug adjuvant ( Ismail et al., 2023 ).…”
Section: T Gondiimentioning
confidence: 99%
“…Moreover, several studies have reported the promising antineoplastic activity of some protozoa as they can inhibit the growth of a variety of tumors or prolong the survival of tumor-bearing animals such as Trichomonas vaginalis [5,6], Trypanosoma [7,8], Toxoplasma gondii [9][10][11] and Plasmodium species [12,13]. Also, helminthic parasites have gained a respectable reputation for their anti-tumor properties, such as Echinococcus granulosus [14,15] and Trichinella spiralis (T. spiralis), which can adversely affect tumor growth and extend the host lifespan [4,16,17].…”
Section: Introductionmentioning
confidence: 99%